Digital Funds of Identity: Funds of Knowledge 2.0 for the digital generation? - Poole, Adam (2016)
This paper is a theoretically orientated analysis that synthesises the literature on Funds of Identity with the literature on digital identities. It makes the case for considering Funds of Identity as more than just an enrichment of the Funds of Knowledge approach by suggesting that it is in fact a development. This article also extends the concept and methodology of Funds of Identity by situating identity within a digitised interpretation of social interaction. It does this by exploring the role that avatars and virtual learning environments could play in the development of online identities and their potential application within the classroom. The literature on funds of identity is then synthesised with the literature on new technology, identity and digital literacies This article also explains how digital funds of identity could be used in relation to domain specific knowledge which is illustrated by focusing on English literature and secondary education.